2017
DOI: 10.1007/s10964-017-0642-3
|View full text |Cite
|
Sign up to set email alerts
|

Purpose and Character Development in Early Adolescence

Abstract: Character development in adolescence is of growing interest among psychology researchers and educators, yet there is little consensus about how character should be defined and studied among developmental scientists. In particular, there is no fully developed framework for investigating the developmental relationships among different character strengths. This study examines the developmental relations between purpose and three other key character strengths that emerge during early adolescence: gratitude, compas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 48 publications
1
61
1
15
Order By: Relevance
“…As with other forms of risk taking, positive risk taking can help youth achieve developmental milestones such as autonomy and the acquisition of skills (Ellis et al, 2012;Spear, 2013). Positive risk taking may also create opportunities for youth to develop a sense of purpose (Malin, Liauw, & Damon, 2017) and identity (e.g., by standing up for one's beliefs), personal responsibility (e.g., by playing sports on a team), and social competence (e.g., by initiating friendships), as well as to set goals (e.g., by taking challenging courses). Over time, and combined with other positive influences, these may yield additional benefits such as school engagement and academic success (e.g., Wood et al, 2013), perseverance or grit (Duckworth & Gross, 2014), or positive socioemotional functioning (e.g., Crone & Dahl, 2012).…”
Section: Measuring Positive Risk Takingmentioning
confidence: 99%
“…As with other forms of risk taking, positive risk taking can help youth achieve developmental milestones such as autonomy and the acquisition of skills (Ellis et al, 2012;Spear, 2013). Positive risk taking may also create opportunities for youth to develop a sense of purpose (Malin, Liauw, & Damon, 2017) and identity (e.g., by standing up for one's beliefs), personal responsibility (e.g., by playing sports on a team), and social competence (e.g., by initiating friendships), as well as to set goals (e.g., by taking challenging courses). Over time, and combined with other positive influences, these may yield additional benefits such as school engagement and academic success (e.g., Wood et al, 2013), perseverance or grit (Duckworth & Gross, 2014), or positive socioemotional functioning (e.g., Crone & Dahl, 2012).…”
Section: Measuring Positive Risk Takingmentioning
confidence: 99%
“…Using cross-sectional analyses, the authors found a small but significant relationship between purpose and the other three strengths of interest: gratitude, compassion, and grit. Like Froh et al (2010), who identified that gratitude may motivate students towards contributing to their communities, Malin et al (2017, in this special section) identified that "qualitative differences in gratitude and compassion between those with full purpose and those who are not yet realizing their purposeful aspirations" (p. 12).…”
Section: Relationships Among Character Strengthsmentioning
confidence: 96%
“…Perhaps even more significant than their discussion of the relationship between character strengths, Malin et al (2017, in this special section) note, For most people during most of development, character is far from unitary. Feelings, thoughts, and actions related to virtues may be frequently misaligned; and the virtues (or "character strengths") themselves may develop at an uneven pace, with some maturing while others grow slowly or not at all.…”
Section: Individual Profilesmentioning
confidence: 99%
See 2 more Smart Citations